THE COOL GIANT STARS AND CHEMICAL EVOLUTION OF GALAXY - Komarov, N. S.; Shevchuk, T. V. (Одеські астрономічні публікації, 2017)
The fundamental characteristics and abundances of cool giant stars is discussed. The possible evolution of nuclides in process evolution of Galaxy was very shortly described.